AMINO ACID SEQUENCE MOTIVE OF OSELTAMIVIR BINDING POCKET IN NEURAMINIDASE PROTEIN OF AVIAN INFLUENZA (H5N1) VIRUS FROM HUMAN AND ANIMAL IN INDONESIA - Kade Mahardika, I Gusti Ngurah; Sukada, I Made; Suma Antara, Made; Suartini, I Gusti Ayu (Jurnal Veteriner, 2008)
Former finding that avian influenza (AI) virus of H5N1 subtype from Indonesia shows reduced sensitivity against oseltamivir is critically reviewed trough molecular observation of the amino-acid sequence motive of neuraminidase protein (NA) of all H5N1 virus from human and animal in Indonesia available in GeneBank. Amino acid sequence of oseltamivir binding pocket of NA protein on all Indonesian viruses is typical for sensitive virus with a concerved motive of H274, E276, R292 dan N294. Resistance issue could not be explained based on available data.